Forecasting the future path of HIV prevalence among individuals aged 15-49 years in Colombia using Holt’s double exponential smoothing model (Texas Journal of Medical Science, 2024)
This study uses annual time series data of HIV prevalence among individuals aged 15-49 years for Colombia from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s double exponential smoothing model. The optimal values of smoothing constants α and β are 0.9 and 0.1 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15-49 years will remain around 0.4% throughout the out of sample period. Therefore, we encourage authorities to scale up HIV case detection, treatment and prevention especially among key populations and vulnerable groups.